Spatial and temporal variation of Dona Francisca reservoir (Jacuí river, Rio Grande do Sul State), a subtropical reservoir - doi: 10.4025/actascibiolsci.v34i3.10078 - Leon Maximiliano Rodrigues; Albano Schwarzbold; Maria Angélica Oliveira (Acta Scientiarum. Biological Sciences, 2012)
The present study examined the behavior of a reservoir located on subtropical latitude (Dona Francisca reservoir). The limnological variables measured were dissolved oxygen, temperature, pH and electric conductivity. Measurements were taken quarterly at different sampling sites along the reservoir. The results indicated the formation of longitudinal zones regarding circulation patterns and stratification, beyond the influence from the water masses of the main tributary. The vertical profiles were obtained. The behavior of the reservoir is similar to others previously studied in the country, but with shorter time-lag stratification and a narrower range, possibly due to the shorter residence time of the water, and to the latitude, where summer is shorter.